Effects of post-tetanic potentiation induced by whole-body electrostimulation and post-activation potentiation on maximum isometric strength - Dote-Montero, Manuel; Pelayo-Tejo, Ignacio; Molina-Garcia, Pablo; Carle-Calo, Abraham; García-Ramos, Amador; Chirosa-Ríos, Luis J.; Chirosa-Ríos, Ignacio J.; Amaro-Gahete, Francisco J. (Biology of Sport, 2022)
It is currently unknown the most effective potentiation protocol to increase maximum strength. Hence, we investigated the separated and combined effects of post-tetanic potentiation (PTP) induced by wholebody electrostimulation (WB-EMS) and post-activation potentiation (PAP) induced by voluntary maximum isometric contractions on maximum isometric strength. Ten trained males were randomly evaluated on four occasions. In session A, maximum isometric strength (split squat) was measured in minutes 1, 4, and 8. In session B, the measurements were taken in minutes 2, 6, and 10. In session C, a WB-EMS protocol was applied to elicit PTP and the measurements were performed in minutes 1, 4, and 8. In session D, the same WB-EMS protocol was applied and the measurements were taken in minutes 2, 6, and 10. No significant differences in maximum isometric strength were observed between: (i) the control and WB-EMS in minutes 1 vs. 1 and 2 vs. 2; (ii) the control and PAP in minutes 1 vs. 4, 1 vs. 8, 2 vs. 6, and 2 vs. 10; and (iii) the PAP and WB-EMS plus PAP in minutes 4 vs. 4, 8 vs. 8, 6 vs. 6, and 10 vs. 10. In contrast, the WB-EMS plus PAP revealed a significant increase of 54% (~450 N) compared to the WB-EMS in minutes 4 and 8 compared to the minute 1 (p < 0.001), but not between minutes 2 vs. 6 and 2 vs. 10. The present results showed that PTP induced by WB-EMS in isolation or combined with PAP induced by voluntary maximum isometric contractions did not produce a significant increase in maximum isometric strength compared to the control and PAP alone, respectively.